Scaffolding for Algebra Errors From the Perspective of Emotional Quotient - Hervilia, Era; Subanti, Sri; Pramudya, Ikrar; Nugroho, Purwo Setiyo (FKIP Universitas Lampung, 2024)
Abstract: Mathematical understanding, particularly algebra, is essential in education. One effort to reduce student errors in learning can be achieved through an in-depth study of the relationship between students' emotional intelligence and the learning process. Emotional intelligence in learning mathematics is the ability to control one's emotions, manage, and express emotions towards others. Emotional intelligence is crucial for understanding the lessons delivered by the teacher. This research aims to investigate the relationship between student errors and the level of emotional intelligence by applying scaffolding to middle school students. The method used in this study is the correlational research method because it aims to determine the relationship between variable X (emotional intelligence) and variable Y (errors). The study population consisted of eighth-grade students at SMPN 1 Saradan in the 2022/2023 academic year, distributed in one class with a total of 30 students. From this class, 3 students were randomly selected as samples using purposive sampling technique. The instruments used in this research were an emotional intelligence questionnaire about mathematics and a mathematics error test on algebra material. The data processing and analysis technique in this study used correlation tests. The results of the correlation test in this study show that there is a significant relationship between emotional intelligence in mathematics and students' mathematical errors, with a correlation coefficient of 0.887, indicating a strong correlation. Based on these results, the conclusion can be drawn that students with high, moderate, and low emotional intelligence will produce better mathematics learning outcomes with the application of scaffolding. This activity is crucial, especially for teachers to understand students' difficulties and errors, aligning with the teachers' ability to better recognize students' characteristics. Keywords: emotional quotient, newman’s errors, algebraic arithmetic operations, scaffolding.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp236-247